Social capital, regional development and innovation in Greece: an interregional analysis. (26th September 2019) - Ierapetritis, Dimitrios G.
The term social capital tends to appear more and more in international literature as a major factor for accessing new sources of knowledge and information, creating innovation and supporting regional innovation systems. The main objective of this paper is to contribute insights to this stream of research by testing empirically the impact of social capital on innovation at the level of NUTS-2 and more specifically, on the 13 regions of Greece. The paper begins by defining social capital along with the various forms that this can acquire, the ways that social capital is measured internationally as well as its role in regional development. The above is followed by a close study of the contribution of social capital to the diffusion of knowledge and the strengthening of regional innovation. Finally, by evaluating and exploiting the results of the recent researches by the European social survey (ESS) and the regional innovation scoreboard (RIS) on the 13 Greek regions (NUTS-2) the paper will firstly present the available social capital reserves, secondly the most recent regional innovation performance and thirdly it will test to what extent social capital can be a source of high performance of regional innovation.